2012
DOI: 10.1175/bams-d-11-00015.1
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Automatic Weather Station Program: 30 Years of Polar Observation

Abstract: Antarctica boasts one of the world's harshest environments. Since the earliest expeditions, a major challenge has been to characterize the surface meteorology around the continent. In 1980, the University of Wisconsin—Madison (UW-Madison) took over the U.S. Antarctic Program (USAP) Automatic Weather Station (AWS) program. Since then, the UW-Madison AWS network has aided in the understanding of unique Antarctic weather and climate. This paper summarizes the development of the UW-Madison AWS network, issues rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(174 citation statements)
references
References 29 publications
1
159
0
Order By: Relevance
“…The temperature readings were collected by professional weather observers until the 1970s, providing a robust anchor for the early portion of record. The operation of the AWS has proved more challenging in the harsh Antarctic environment, but the origins of the data gaps are well understood 21 . Global atmospheric reanalyses are, in principle, uniquely suited for our reconstruction.…”
Section: Improved Temperature Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature readings were collected by professional weather observers until the 1970s, providing a robust anchor for the early portion of record. The operation of the AWS has proved more challenging in the harsh Antarctic environment, but the origins of the data gaps are well understood 21 . Global atmospheric reanalyses are, in principle, uniquely suited for our reconstruction.…”
Section: Improved Temperature Estimatesmentioning
confidence: 99%
“…The observations from the initial year-round occupied station (1957)(1958)(1959)(1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975) are combined with updated and corrected data from the automatic weather station (AWS) maintained since 1980 by the US Antarctic AWS Program 21 . Missing observations are estimated using adjusted temperature data from the ERA-Interim reanalysis 22 for 1979-2012 and, before 1979, a combination of global reanalysis data and spatially interpolated observations from other Antarctic sites.…”
mentioning
confidence: 99%
“…The data used in the analysis are the interpolated dataset to 0.1258 from the native T255 horizontal using Meteorological Archival and Retrieval System (MARS). Surface meteorological observations are obtained from the University of Wisconsin (UW) automatic weather station program (Lazzara et al 2012) to understand meteorological conditions as well as the synoptic background associated with SWE. Further details regarding UWAWSs used in this study can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The model is forced by a long-term surface temperature trend based on published records by Van Ommen et al (1999), DahlJensen et al (1999) and Orsi et al (2012). A generic Antarctic seasonal cycle derived from a ~8-10-year climatology of 15 automatic weather station observations at WAIS Divide and Law Dome (Lazzara et al, 2012) is superimposed on this trend.…”
Section: Thermal Fractionation and The Temperature Modelmentioning
confidence: 99%